2005
DOI: 10.1007/bf02893392
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of chromosome 1 and 8 copy number in invasive ductal breast carcinoma among iranian women: An interphase FISH analysis

Abstract: Breast cancer is amongst the leading causes of death in women worldwide and the most common cancer amongst Iranian women. Unfortunately, the current clinical and histological criteria can only help 60 percent of women with breast cancer in diagnosis and long-term treatment. Therefore, genetic markers both at single gene and chromosomal level can play an important role in improving the diagnosis and prognosis of breast cancer patients. The aim of this retrospective study was to investigate the role of chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A limited number of reports have studied a correlation between chromosomal abnormalities and cytological grades of breast cancer 9. The MN score was also correlated with the cytological grades for the first time in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of reports have studied a correlation between chromosomal abnormalities and cytological grades of breast cancer 9. The MN score was also correlated with the cytological grades for the first time in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the screening for CIN may be useful for estimating the biological behavior of cancer patients 7, 8. Although, CIN can be determined by fluorescence in situ hybridization (FISH) based techniques, the availability, and cost of probes limits their use 9. Therefore there is a need to search for the simpler and cheaper methods to assess the presence of CIN in cancer.…”
mentioning
confidence: 99%
“…the cDNA synthesis kit(Fermentas Germany,) has been used. Evaluation of concentration and purity of cDNA was performed using Pico Drop 2000 (Thermo Fischer Scientific Inc) (Behjati et al, 2005;Mowla et al, 2005;Mistry et al, 2008).…”
Section: Cdna Synthesismentioning
confidence: 99%
“…Unfortunately, 70% of Iranian women are diagnosed in advanced stages of cancer when it is late for proper treatment. [23] The low survival rate of breast cancer in developing countries is characterized by a lack of awareness and lack of early detection programs, which leads to a high proportion of women presenting with symptoms of end-stage disease and a lack of adequate facilities for diagnosis and treatment. [14] Continuous increase in breast cancer deaths in Iranian women may be due to the low use of screening tests for breast cancer.…”
Section: Introductionmentioning
confidence: 99%